Local retrofit of exterior RC beam-column joints using thin RC jackets-an experimental study. - Karayannis, Chris G.
The use of a new type of reinforced concrete (RC) jacket for RC exterior beam column connections damaged by seismic excitations is addressed and experimentally investigated. The proposed jacket has very small thickness and includes small diameter steel reinforcement. This jacketing applies at the joint region and at a small part of the columns and the beam. The main advantage of the proposed thin and locally applied jacket compared with the commonly used concrete jacket is the fact that its application is not restrained by space limitations and since it slightly changes the initial size of the elements, the building's dynamics and seismic behaviour remain practically unaffected. For the needs of this study, 10 exterior beam column joint subassemblages were constructed and subjected to increasing cyclic loading. Later, the damaged specimens were locally retrofitted using the proposed thin RC jackets and they were retested with the same load sequence. Three different specimen configurations with various amounts of shear reinforcement in the joint area were examined and two types of jackets (a) with light and (b) with dense reinforcement were applied. Test results indicated that the seismic performance of the retrofitted specimens was fully restored and in some cases subtantially improved with respect to the performance of the same specimens in the initial loading, since they exhibited higher values of load capacity and hysteretic energy dissipation. Discussion for the conditions of the use of the examined jacketing technique either as a repair or as a strengthening method is also included.
Keywords: Beam-column joints; Jacketing; Reinforced concrete; Retrofit; Seismic performance; Tests